GEOLOGI DAN PEMODELAN RESERVOIR BATUPASIR FORMASI BINIO PADA LAPANGAN SS, CEKUNGAN SUMATRA TENGAH - Rebecca Wyanet Clara, Vania
SS Field is one of the gas fields located in Central Sumatra Basin. Administratively, SS Field is located in Riau Province and covers an area of about 467 km2. The objectives of this study are to determine SS Field’s geological setting, to generate static reservoir model, and to estimate initial hydrocarbon in place. The study is focused on four sandstone reservoirs in Binio Formation which are Reservoir 1, Reservoir 2, Reservoir 3 and Reservoir 4. The dataset used in this study includes wireline log of 6 wells, 2D seismic data, cutting and core description data. The methods used in this study consist of four evaluation methods which are: well data analysis by doing well-to-well correlation using sequence stratigraphy concept and petrophysical analysis; seismic data analysis by generating depth structure map and interpreting reservoir geometry; the integration of well data and seismic data; reservoir modeling by generating 3D structure model, generating petrophysical model, determining fluid contact, and estimating initial hydrocarbon in place. The results of these methods are the stratigraphy and structure of SS Field which are derived from the integration of well data and seismic data. Each reservoir interval is sandstone with varied thickness between 1.5 – 12 m as intercalation in shale. Main structure of SS Field is an anticline associated with northwest – southeast trending reverse fault. The depositional facies of Reservoir 1 and Reservoir 4 is barrier-island and estuarine, whereas the depositional facies of Reservoir 2 and Reservoir 3 is barrier-island. The initial gas in place estimation of those reservoirs is 189 BSCF.